Methods for the measurement of fluid flow in pipes Part 1. Pressure differential devices Sec 1.1 Specification for square-edged orifice plates, nozzles and venturi tubes inserted in circular cross-section conduits running full - British Standards Institution (London BSI, 1992)
Flow measurement, Flow, Pipes, Pressure measurement (fluids), Differential-pressure flowmeters, Flowmeters, Orifice flowmeters, Nozzle flowmeters, Venturi meters, Flow nozzles, Venturi tubes, Fluid equipment components, Design, Installation, Position, Flow coefficient, Square shape, Edge
BS 1042 : Sec 1.1 : 1992
Keywords: Fluid flow -- Standards